The factors influencing customer trust in online shopping provided by Groupon HQ Malaysia / Umar Fitri Razali and Nur Amira Hashim - Razali, Umar Fitri; Hashim, Nur Amira (2014)
The purpose of this study is to investigate the influence factors of consumer trust in online shopping provided by Groupon HQ Malaysia. In this study it will help the organization to increase their productivity and organization performance in the online industry. As the Internet is widely used by consumers nowadays, the number of web users grows daily and has surpasses 500 million marks. However not all of the users make and involved in online purchases. Trust is the main factor behind the scenario. Therefore this paper discusses the result of factors that influence the customer trust in online shopping. Analysis of survey responses based on 196 respondents from the consumers of Groupon HQ Malaysia itself found that the most of the variables; reputation of company, privacy protection, security protection and service quality in the study significantly influenced the customer trust.